Üllas Ehrlich – 60 (9.12.1963) - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2024)
Co-organiser and long-term active participant of our conferences (since 2010), author, peer reviewer and editor of the journal Estonian Discussions on Economic Policy, professor of the Tallinn University of Technology (TUT) Dr Üllas Ehrlich – 60 years (09.12.2023). Üllas Ehrlich was Estonia's first and until now the only professor of environmental economics in 2009 until the chair and professorship were abolished in 2020. He was one of the first to lay the foundation for financial evaluation of non-market ecosystem services in Estonia. In addition, his lesser-known field of activity is cost-benefit analyses of large infrastructure objects. For example, the section of the Kukruse-Jõhvi four-lane road, the reconstructed exit of the Tallinn-Tartu road and the connection road to the deep harbor in Saaremaa are based on his profitability calculations. We wish our productive and hard-working colleague good health, success and happiness in his future activities.